The Bacterial Microbiome of the Long-Term Aquarium Cultured High-Microbial Abundance Sponge Haliclona cnidata – Sustained Bioactivity Despite Community Shifts Under Detrimental Conditions - Schellenberg, Johannes; Reichert, Jessica; Hardt, Martin; Klingelhöfer, Ines; Morlock, Gertrud; Schubert, Patrick; Bižić, Mina; Grossart, Hans-Peter; Kämpfer, Peter; Wilke, Thomas; Glaeser, Stefanie P. (Frontiers in Marine Science, 2020)
Marine sponges host highly diverse but specific bacterial communities that provide essential functions for the sponge holobiont, including antimicrobial defense. Here, we characterized the bacterial microbiome of the marine sponge Haliclona cnidata that has been in culture in an artificial marine aquarium system. We tested the hypotheses (1) that the long-term aquarium cultured sponge Haliclona cnidata is tightly associated with typical sponge bacterial microbiota and (2) that the symbiotic Bacteria sustain bioactivity under harmful environmental conditions to facilitate holobiont survival by preventing pathogen invasion. Microscopic and phylogenetic analyses of the bacterial microbiota revealed that H. cnidata represents a high microbial abundance (HMA) sponge with a temporally stable bacterial community that significantly shifts with changing aquaria conditions. A four week incubation experiment was performed in small closed aquaria systems with antibiotic and/or light exclusion treatments to reduce the total bacterial and photosynthetically active sponge-associated microbiota to a treatment specific resilient community. While the holobiont was severely affected by the experimental treatment (i.e. fading of the sponge, reduced bacterial abundance, shifted bacterial community composition), the biological defense and bacterial community interactions (i.e. quorum sensing activity) remained intact. 16S rRNA gene amplicon sequencing revealed a resilient community of 105 bacterial taxa, which remained in the treated sponges. These 105 taxa accounted for a relative abundance of 72-83% of the bacterial sponge microbiota of non-treated sponge fragments that have been cultured under the same conditions. We conclude that a sponge-specific resilient community stays biologically active under harmful environmental conditions, facilitating the resilience of the holobiont. In H. cnidata, bacteria were located in bacteriocytes, which may have contributed to the observed phenomenon.